Maruyama Masao : and the Fate of liberalism in Twentieth-Century Japan - Tadashi, Karube (LTCB International Library Selection ;, 2008)
The Fate of a Thinker -- A taisho Kid -- In a politicized age -- From war to postwar -- Conceiving postwar democracy -- Politics and humanity in the contemporary world -- The sense of otherness -- Chronology -- Notes.